2022
DOI: 10.14202/vetworld.2022.1481-1488
|View full text |Cite
|
Sign up to set email alerts
|

First study of in vitro protective effect of Lepidium meyenii (Maca) on frozen–thawed bovine spermatozoa

Abstract: Background and Aim: Lepidium meyenii Walp (Maca) is an herbaceous plant that grows in the Peruvian Andes and it has been widely used as a nutritional supplement and fertility enhancer and has been used in the treatment of a variety of diseases, such as rheumatism, respiratory disorders, and anemia. The most notable feature of Maca is its potent antioxidant capacity, which helps in the scavenging of free radicals and protection of cells from oxidative stress. This study aimed to evaluate the in vitro effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…In another study, the use of aqueous extract in the preservation of sperm exposed to freezing evidenced an increase in sperm hyperactivation and the preservation of sperm DNA integrity at 24 h ( Prete et al, 2022 ). Both studies agreed that these effects occur at low doses ( Leiva-Revilla et al, 2022 ; Prete et al, 2022 ); while high doses (≥50 μL/mL) exhibited immediate harmful effects on seminal quality ( Prete et al, 2022 ).…”
Section: Pharmacologymentioning
confidence: 67%
See 2 more Smart Citations
“…In another study, the use of aqueous extract in the preservation of sperm exposed to freezing evidenced an increase in sperm hyperactivation and the preservation of sperm DNA integrity at 24 h ( Prete et al, 2022 ). Both studies agreed that these effects occur at low doses ( Leiva-Revilla et al, 2022 ; Prete et al, 2022 ); while high doses (≥50 μL/mL) exhibited immediate harmful effects on seminal quality ( Prete et al, 2022 ).…”
Section: Pharmacologymentioning
confidence: 67%
“…This was one of the first claim about maca properties to be studied; ten recent preclinical studies were found, mostly aimed at male fertility. In vitro studies evaluated the effect of different maca extracts on cells of the male reproductive system, including Sertoli cells ( Yoshida et al, 2018 ) and sperm ( Leiva-Revilla et al, 2022 ; Prete et al, 2022 ). The hydroalcoholic extract increased testosterone production by Leidig cells and was involved in steroidogenesis; however, this steroidogenic effect declined with increasing age ( Ybañez-Julca et al, 2022 ).…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, several studies reported the effectiveness of maca on improving semen quality and quantity in stallions (Del Prete et al, 2018), humans (Tafuri et al, 2021) and canine (Del Prete et al, 2022). Besides that, Leiva-Revilla et al (2022) could be reported that in bovine semen the four dilutions of maca extract at 0, 1, 10, and 100 mg/mL post-thawing incubation for 24 hours indicated rectilinear motility up to 49,60,53 and 48 %,normal 88,90,87 and 87 %,intact live acrosome 21,25,40 and 30%,livability 22,25,41 and 30% and normal DNA 90.60,92.29,91.35 and 91.44%,respectively. Then, the best of aqueous extract of maca on ram semen extenders during the short-term storage at 5 °C for 5 days may be related to antioxidant activity. In this context, Buyanbadrakh et al (2020) who revealed that macaridine, macaene, macamides and alkaloids in maca has freeradical scavenging capacity and increase the levels of superoxide dismutase and glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, polyunsaturated fatty acids are presented in maca which played beneficial role in protected cell membrane of spermatozoa. In this assay, Leiva-Revilla et al (2022) reported that normal head was 3, 3, 2 and 4% and fragmented DNA was 9.40, 7.71, 8.65 and 8.56 % post-thawing in bovine semen extender incubation for 24 hours contained 0, 1, 10, and 100 μg/mL of maca extract, respectively. On the other hands, elements in maca can be able to activate sperm function (Kerns et al, 2018) who noticed that elements are known to play an important role for reproduction performance, specially zinc (Zn) are essential for reproduction and that their deficiency can lead to degenerative changes of sperm activity.…”
Section: Discussionmentioning
confidence: 99%